The Significance of Rasayana in Madhumeha (Diabetes): A Review Article. - Sharma, Ketan; Kumari, Shailza; Veena; Raghuwanshi, Manoj Singh (International Research Journal of Ayurveda & Yoga, 2023)
Diabetes mellitus is one of the major metabolic diseases characterized by hyperglycemia performing from blights in insulin stashing, insulin action, or both. Diabetes is associated with long-term potential effects on almost all systems of the body, leading to various complications. Due to change in food habits and lifestyle, the cases of diabetes are increasing rapidly. Diabetes which has been a global problem is well described in the ancient Ayurveda science. Boosting immunity is essential to fight disease and other complications. As described by Charaka a person can attain Dheergaayu Smriti, Medha (Learning Power), Arogya, youthfulness (tarun),vaya(age), Bala(strength), Utsaha(enthusiasm), vakasauṣṭhava (proper speech) and such other healthy qualities by using a Rasayana. Ajasrika Rasayana in the form of healthy food and Naimitika Rasayana like Shilajita, Haritaki,Amalaki,Triphala etc. have been mentioned in Ayurveda for treatment of Diabetes mellitus.In addition to this proper behavorial region is mentioned in form of Achara Rasayana. Rasayana should be taken according to vaya, prakriti , satmya and severeity of disease. Due to the chronicity of diabetes, complications like Manodourbalyam & Indriyadaurbalyata also occur. Rasayana should be used in Madumeha chikitsa according to rog-rogi bala. The detailed description of matter has been given in full paper.